Parental involvement and Children's internet uses - Relationship with parental role construction, self-efficacy, internet skills, and parental instruction - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Computers & Education)
Internet use is significant in the everyday lives of children and can be distinguished into different uses (e.g., entertainment-related, informative or school-related). When considering the literature on internet inquiries, the family as an informal place of learning is of particular importance. Although some predictors within the family (e.g., structural factors) are widely researched, comprehensive results on the influence of parental involvement, especially parental instruction as a form of parental support during information-related internet activities, on different internet uses are still lacking. Therefore, the study investigates (1) the relationship of parental role construction, self-efficacy, internet skills, and parental instruction in information-related internet use perceived by parents and children and (2) the relationship of parental role construction, self-efficacy, internet skills, parental instruction, and children's internet uses at home (entertainment-related, practical and school-or-learning-related). The mediation effects of parental instruction were also tested. A paper-and-pencil questionnaire was answered by 361 German children and their parents. Structural equation modeling was applied to answer the research questions. We observed that children's perceived parental instruction was positively associated with children's practical and school-or-learning-related internet use. Parents' motivational factors were the strongest predictors for parents' perceived parental instruction The findings have significant implications for research and practice on how parents can be more active in fulfilling their role as supporters for children's internet use.

Voluntary Submission and the ʻPolitics of Truth’: Nietzsche and Foucault on the Danger of the Fully Normalised ‘Last Human’ - Corall, Niklas (Nietzsche and the Politics of Difference)

Warum Personalführung in Start-ups anders funktioniert - Hubner-Benz, Sylvia

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

New aspects of modeling and operation of nitrous gas absorption in packed columns - Mackowiak, Jan F.; Franke, Patrick; Chromik, Reiner; Mackowiak, Jerzy (Proceedings of the 12th International Conference Distillation & Absorption Toulouse)

Eye-Tracking Studie zu Textaufgaben in Klasse 5: Bemerken und Interpretieren syntaktischer Strukturen - Dröse, Jennifer; Neugebauer, P.; Delucchi Danhier, R.; Mertins, B. (Eye-Tracking in der Mathematik- und Naturwissenschaftsdidaktik. Forschung und Praxis)

Teacher expertise for fostering at-risk students’ understanding of basic concepts: conceptual model and evidence for growth - Prediger, S.; Dröse, Jennifer; Stahnke, R.; Ademmer, C. (Journal of Mathematics Teacher Education)

Prosepctive teachers‘ diagnostic judgements on students’ under- standing of conditional probabilities - Dröse, Jennifer; Griese, B.; Wessel, Lena (Twelfth Congress of the European Society for Research in Mathematics Education (CERME12))

Weiterentwicklung eines physikdidaktischen Tests zum Online-Assessment - Jordans, Melanie; Zeller, Jannis; Große-Heilmann, Rike Isabel; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung virtuell 2021)

Ansätze zur Ermittlung von Kompetenzniveaus im Fachdidaktischen Wissen - Zeller, Jannis; Jordans, Melanie; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung virtuell 2021)